2015
DOI: 10.1063/1.4930039
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar resistive memory switching with all four possible resistive switching modes in amorphous LaHoO3 thin films

Abstract: We studied the resistive memory switching in pulsed laser deposited amorphous LaHoO 3 (a-LHO) thin films for non-volatile resistive random access memory (RRAM) applications.Nonpolar resistive switching (RS) was achieved in Pt/a-LHO/Pt memory cells with all four possible RS modes (i.e., positive unipolar, positive bipolar, negative unipolar, and negative bipolar) having high R ON /R OFF ratios (in the range of ~10 4 -10 5 ) and non-overlapping switching voltages (set voltage, V ON ~ ± 3.6˗4.2 V and reset voltag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…We have also measured the temperature-dependent resistance variation of the ReRAM device; the results showed that the resistance increases upon increasing the measuring temperature in the LRS (not shown here), which proves that the filament is really composed of metal ions. The same results are also reported in literature [ 18 , 19 , 20 ].…”
Section: Resultssupporting
confidence: 91%
“…We have also measured the temperature-dependent resistance variation of the ReRAM device; the results showed that the resistance increases upon increasing the measuring temperature in the LRS (not shown here), which proves that the filament is really composed of metal ions. The same results are also reported in literature [ 18 , 19 , 20 ].…”
Section: Resultssupporting
confidence: 91%
“…In the case where the mean free path of the electrons is less than the Schottky barrier width, Simmons' modified Schottky equation (Equation (2)) is more appropriated [72,73].…”
Section: Schottky Emissionmentioning
confidence: 99%
“…There are many kinds of memory devices based on different mechanisms and materials that are highly likely to replace non-volatile memory, such as resistive random access memory (ReRAM), ferroelectric RAM (FeRAM), magnetic RAM (MRAM), and phase change memory (PCM) [1][2][3][4][5][6]. Among these new types of memory, resistive switching (RS) memory has been widely studied due to such advantages as its simple preparation process, low energy consumption, predominant memory density, small size, and good compatibility with the conventional CMOS process [7,8]. The ReRAM memory device is a novel non-volatile memory based on the principle of resistance change of thin film materials [9,10].…”
Section: Introductionmentioning
confidence: 99%